Blueprint for low carbon scenarios for asian region- the case of Iskandar Malaysia - Ho, Chin Siong (2013)
Malaysian government aims to reduce 40% reduction of carbon emission intensity by the year 2020 using 2005 as the base year. Several mitigation and adaptation strategies in addressing environmental and climate change are formulated at national, regional and local level to mitigate greenhouse gases. This paper aims to examine local and regional resilient policy actions to reduce greenhouse gases using the empirical case of Iskandar Malaysia. The study case is selected because it is one of the fast developing economic corridor regions in Malaysia. In this study, a low carbon society blueprint is initiated to guide the rapid development of this economic corridor towards low carbon green growth. The blueprint provides the sustainable green growth roadmap with major 12 actions for the region. It is done through a bottom-up approach where stakeholder discussions are carried out to allow local communities participation in the plan formulation.